Chapter 7 Crafting Psychiatric Contention Through Single-Panel Cartoons - Spandler, Helen (Penn State University Press, 2020)
This chapter explores the role of cartoons in contesting psychiatric knowledge and practice. It suggests that cartoons are an increasingly important element in the growing repertoire of contention of the psychiatric survivor movement. It explores how survivor activists have drawn on creative countercultural traditions of art and subversion to create new styles of psychiatric contention. Specifically, it examines the unique role of single-panel cartoons in actively challenging prevailing notions of normalcy, treatments and systems. It presents some cartoons that appeared in the UK-based magazine Asylum magazine from 1986-2016 and analyses how they are used to articulate key themes of psychiatric contention: ECT; self-harm; psychiatric diagnosis; and recovery. It suggests the cartoons encapsulate key psychiatric critiques and communicates their critical messages in a vivid, accessible and often humorous way. Moreover, the author suggests they are a distinctive form of what Arthur W Frank has called 'survivorship as craft' and tentatively suggests they are a particular 'style' of contestation, created by psychiatric survivors.